Faqihuddin Abdul Kodir's Reasoning on Maintenance: The Epistemological Perspective of Bayāni, Burhāni, and Irfāni - Ni'ami, Mohammad Fauzan; Izzuddin, Ahmad; Widyasari S, Citra; Amrullah, Abdul Karim (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
The reinterpretation of the concept of maintenance (nafaqah) plays a pivotal role in defining familial roles. However, maintenance is generally interpreted as the husband’s obligation as the head of the family. This article delves into the epistemological reasoning of Faqihuddin Abdul Kodir in redefining the concept of maintenance within a modern context. Employing conceptual and philosophical approaches, the article reveals that the maintenance concept introduced by Kodir is a product of epistemological reasoning encompassing bāyani, burhāni, and irfāni dimensions. Bāyani reasoning is demonstrated through an understanding approach, and the tabdīl (replacement) method used to analyze maintenance texts. Burhāni reasoning is supported by rational thinking, utilizing primary and minor premises derived from the current phenomena within family dynamics. Irfāni reasoning is evidenced through the elucidation of meaning by Kodir, specifically regarding maintenance texts as a project for the development of divine law (al-aḥkām al-ilāhiyyah) based on the values of love and compassion (raḥmatan lil 'ālamin). This reformulation has implications for methodological and practical innovations regarding maintenance in local and global contexts.